“Who is really British anyway?”: A thematic analysis of responses to online hate materials - Rohlfing, Sarah and Sonnenberg, Stefanie (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2016)
This article aims to add to the relatively small body of literature on online hatred. In particular, it focuses on the role social networking sites may play in the development of polarisation, by exploring how online users respond to explicit online hate materials. Specifically, this article discusses the ways in which a self-selected sample of YouTube users responded, via posting online comments, to a video clip in which a White female train passenger (called Emma) could be seen to racially to abuse other passengers. Thematic analysis of the YouTube comments identified four main themes: (1) Making Sense of Emma, which encapsulated posters' attempts to find explanations for Emma’s behaviour; (2) Meeting Hatred with Hatred, which described posters’ attempts to oppose Emma’s racism by means of resorting to aggressive, hateful language; (3) Us versus Them, which encapsulated posters' tendencies to categorise themselves and other posters into in- and outgroups, based on their particular stance on racism; (4) Contesting Britishness, which expressed posters' attempts to articulate (and contest) what it means to be British. Whilst the current analysis provides some evidence that hateful web content can fuel aggressive and hateful responses, many of the comments analysed here emphasised common group membership, alongside people’s right to claim membership in a particular social category (i.e. Britishness). The current evidence, therefore, suggests that, at least in the specific context of this study, hateful web content may not necessarily lead to an automatic endorsement or escalation of hatred.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTgxNy9jcDIwMTYtNC0y